THE POTENCY OF Bacillus sp. AND Pseudomonas sp. AS BIOLOGICALCONTROL AGENTS AGAINST CORN LEAF BLIGHT DISEASE CAUSED BY Pantoea sp. - Javandira, Cokorda; Aini, Luqman Qurata; Sugiharto, Ariffin Noor; Abadi, Abdul Latief (AGRIVITA, Journal of Agricultural Science, 2013)
One of new biotic constraints in corn production in Indonesia is leaf blight disease caused by Pantoea sp. which is needed to be controlled. The purpose of this research is to study the potential of Bacillus sp. and Pseudomonas sp. as biological control agents against corn leaf blight caused by Pantoea sp. The results showed that all bacterial strains of Bacillus sp. and Pseudomonas sp. have potential in inhibiting the growth of Pantoea sp. by showing the clear zone on the agar plate. The antibiosis types are bactercide or bacteriostatic. On pot experiment all bacterial strains showed the reduction of the disease incidence at the same level compared with that of bactericide streptomycin suphate. All bacterial strains as well as bactericide could reduce the disease incidence at 18-24% compared with that of control (aquades treatment only). The results suggest that all bacterial strains are potential as biological control agent against leaf blight disease on corn leaf caused by Pantoea sp.Keywords: Biological control, Bacillus sp., Pseudomonas sp. and Pantoea sp.